Amino Acid Content in Hulled and Hull-Less Barley Varieties - U. T. Jumanov; T. X. Kuliyev; M. Sh. Xudoynazarov; M. Choriyev; L. Yudosheva (American Journal of Biology and Natural Sciences, 2026)
This article presents data on the amino acid content in hulled and hull-less barley varieties. The research objects included the hull-less barley variety “O‘zbekiston-30” and the hulled barley variety “Bolg‘ali”. The amino acid content in grain composition was determined in the laboratory of the Research Institute of Agrobiotechnology and Biochemistry, Gulistan State University. The obtained results showed that the total amino acid content in hulled barley grain was 39.02 mg/g, while in hull-less barley it was 45.68 mg/g. It was noted that lysine is one of the limiting amino acids. Its content was determined to be 0.422 mg/g and 0.500 mg/g, respectively. It was also established that the proportion of essential amino acids in hull-less barley is 15–16% higher compared to hulled barley.